Plasminogen Activator Production Accompanies Loss of Anchorage Regulation in Transformation of Primary Rat Embryo Cells by Simian Virus 40 - Pollack, R. (1974)
We have isolated several lines of rat embryo cells transformed by simian virus 40. All these lines are fully transformed with regard to saturation density and serum sensitivity, but they differ greatly in their anchorage dependence, as assayed by efficiency of plating in methyl cellulose suspension. This set of lines reveals a consistent relation of plasminogen activator production to plating efficiency in methyl cellulose. T-antigen-positive transformed lines that synthesize activator grow in methyl cellulose suspension, while T-antigen-positive transformed lines that do not synthesize activator fail to form colonies in suspension. Normal rat embryo cells produce very little plasminogen activator and do not grow in methyl cellulose. Sera that permit high levels of plasmin formation and activity support growth in semi-solid medium better than sera whose plasminogen is activated poorly and/or sera that contain inhibitors to plasmin.